Handbook of corrosion engineering. - Roberge, Pierre R., ....- (New York : McGraw-Hill, 2000)
Ch. 1 Aqueous Corrosion Ch. 2 Environments Ch. 3 High-Temperature Corrosion Ch. 4 Modeling, Life Prediction and Computer Applications Ch. 5 Corrosion Failures Ch. 6 Corrosion Maintenance Through Inspection And Monitoring Ch. 7 Acceleration and Amplification of Corrosion Damage Ch. 8 Materials Selection Ch. 9 Protective Coatings Ch. 10 Corrosion Inhibitors Ch. 11 Cathodic Protection Ch. 12 Anodic Protection App. A SI Units App. B: Glossary App. C Corrosion Economics App. D Electrochemistry Basics App. E Chemical Compositions of Engineering AlloysApp. F Thermodynamic Data and E-pH DiagramsApp. G Densities and Melting Points of Metals